2008
DOI: 10.1186/1471-213x-8-99
|View full text |Cite
|
Sign up to set email alerts
|

Varicose: a MAGUK required for the maturation and function of Drosophila septate junctions

Abstract: Background: Scaffolding proteins belonging to the membrane associated guanylate kinase (MAGUK) superfamily function as adapters linking cytoplasmic and cell surface proteins to the cytoskeleton to regulate cell-cell adhesion, cell-cell communication and signal transduction. We characterize here a Drosophila MAGUK member, Varicose (Vari), the homologue of vertebrate scaffolding protein PALS2.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
36
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(38 citation statements)
references
References 69 publications
2
36
0
Order By: Relevance
“…To do so, we tested whether depletion of Varicose, a MAGUK protein required for septate junction assembly and function (Bachmann et al, 2008; Moyer and Jacobs, 2008; Wu et al, 2007), was able to suppress the wheezy tube dilation defect. We found that transition zone tube dilation was completely suppressed in 52% of terminal cells and partially suppressed in another 20%, while an additional 9% of cells actually showed the discontinuous tube (“gap”) defect characteristic of lotus (n=48) (Figure 6F).…”
Section: Resultsmentioning
confidence: 99%
“…To do so, we tested whether depletion of Varicose, a MAGUK protein required for septate junction assembly and function (Bachmann et al, 2008; Moyer and Jacobs, 2008; Wu et al, 2007), was able to suppress the wheezy tube dilation defect. We found that transition zone tube dilation was completely suppressed in 52% of terminal cells and partially suppressed in another 20%, while an additional 9% of cells actually showed the discontinuous tube (“gap”) defect characteristic of lotus (n=48) (Figure 6F).…”
Section: Resultsmentioning
confidence: 99%
“…The requirement of MPP6 was reported for the maturation and function of Drosophila septate junctions (20). In addition, other MAGUKs, such as Dlg1 (5,6,8,13) and MPP5 (25), were reported to affect myelination if they were deficient due to the disruption of the phosphatidylinositol metabolism with Mtmr-2 (myotubularin-related 2) and PTEN (phosphatase and tensin homolog).…”
Section: Discussionmentioning
confidence: 99%
“…Mutations disrupting chitin biosynthesis ( krotzkopf verkehrt and mummy/cystic ) and matrix assembly ( knickkopf and retroactive ) grow over-dilated tubes (Araujo, et al 2005; Devine, et al 2005; Moussian, et al 2006). In contrast, mutations affecting chitin modification ( vermiform and serpentine ) (Luschnig, et al 2006) and septate junctions (SJ, analogous to vertebrate tight junctions) lead to longer tubes (Behr, et al 2003; Paul, et al 2003; Llimargas, et al 2004; Wu, et al 2004; Luschnig, et al 2006; Moyer and Jacobs. 2008; Laprise, et al 2010).…”
Section: Introductionmentioning
confidence: 99%